Fabrication and properties of Cf/Ta4HfC5‐SiC composite via precursor infiltration and pyrolysis. Issue 12 (21st July 2021) - Zou, Xuegang; Ni, Dewei; Chen, Bowen; Ye, Li; Sun, Yanan; Lu, Jun; Cai, Feiyan; Gao, Le; Zhao, Tong; Dong, Shaoming
Abstract: In this study, a Cf /Ta4 HfC5 ‐SiC ultra‐high‐temperature ceramic matrix composite exhibiting a homogeneous phase distribution was successfully fabricated via precursor infiltration and pyrolysis processing. Initially, the pyrolysis and solid solution mechanisms exhibited by the Ta4 HfC5 precursor were investigated and characterized through TG‐MS and XRD analysis. The as‐fabricated Cf /Ta4 HfC5 ‐SiC composite exhibited a density and open porosity of 2.84 g/cm 3 and 10.62 vol%, respectively. It also exhibited outstanding mechanical properties, with a flexural strength of 339 ± 20 MPa and fracture toughness of 11.56 ± 0.77 MPa·m 1/2 . The Cf /Ta4 HfC5 ‐SiC composite demonstrated strong ablation resistance under a heat flux of 5 MW/m 2 at 2400℃, with corresponding linear and mass recession rates of 5.33 μm/s and 6.18 mg/s, respectively. The combination of strong mechanical properties and ablation resistance provides a solid basis for the use of the Cf /Ta4 HfC5 ‐SiC composite in a new generation of ultra‐high‐temperature materials.